1.6k views
2 votes
-6(2x - 3) + 2x
how do i do this? also show your work please

User Mlr
by
6.2k points

2 Answers

5 votes
-6(2x-3) +2x
Distribute the -6 into the parentheses: -12x+18+2x
Combine like terms: -10x+18
User Nikita Ryanov
by
5.8k points
7 votes

Answer:

Hi! I'll do my best to explain for you.

-6(2x-3)+2x =0 First, set the equation equal to zero.

-12x+18+2x=0 Then, distribute the -6 by multiplying it with the -2 and -3.

-10x+18=0 Combine the like terms, which are -12x and 2x, to get -10x.

-10x=-18 You want to get the x on 1 side. Subtract 18 from both sides.

x=-18/-10 Divide by -10 on both sides.

x=1.8 Simplify the fraction. The answer is x=1.8.

I hope this helped!

User Feupeu
by
6.9k points